2016
DOI: 10.1021/acs.nanolett.6b03525
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Generation of Vector Beams From AlGaAs Nanoantennas

Abstract: The quest for nanoscale light sources with designer radiation patterns and polarization has motivated the development of nanoantennas that interact strongly with the incoming light and are able to transform its frequency, radiation and polarization patterns. Here, we demonstrate dielectric AlGaAs nanoantennas for efficient second harmonic generation, enabling the control of both directionality and polarization of 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
253
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 277 publications
(272 citation statements)
references
References 43 publications
11
253
0
2
Order By: Relevance
“…Furthermore, semiconductors provide the possibility of modulating the refractive index via the injection of free carriers (FCs); this effect is quite subtle in metals due to the very high initial electron density. Nonlinear-optical properties of semiconductor metasurfaces were recently found to be improved by orders of magnitude when compared with the respective constituent materials 2126 , paving the way to efficient all-optical tuning.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, semiconductors provide the possibility of modulating the refractive index via the injection of free carriers (FCs); this effect is quite subtle in metals due to the very high initial electron density. Nonlinear-optical properties of semiconductor metasurfaces were recently found to be improved by orders of magnitude when compared with the respective constituent materials 2126 , paving the way to efficient all-optical tuning.…”
Section: Introductionmentioning
confidence: 99%
“…[47,48] In this work, we first analyzed a unit cell of VSRR and found that under x-polarized illumination it induces two SH surface current distributions that generate two categories of SH signals propagating in six different directions, as shown in Figure 4a. The determination of phase modulation by an individual unit cell involves substantial computation and analysis.…”
Section: Stereometamaterialsmentioning
confidence: 99%
“…Recently it has been proposed that all-dielectric high-index nanostructures, for example, composed of Si, Ge, [1] Te, [2] or AlGaAs, [3] can be used as alternatives to plasmonic structures for realization of low-loss nanophotonic platforms more suitable for real-life practical applications. One of the main limitations is related to intrinsic resistive dissipation, which limits the quality factor of their resonances, causes absorption losses, and may lead to unwanted photothermal heating.…”
Section: Chiral Nanoresonatorsmentioning
confidence: 99%
“…A nanostructure possessing a gradient at the nanoscale is fabricated onto a high-quality silicon film previously deposited on a glass wafer. Recently it has been proposed that all-dielectric high-index nanostructures, for example, composed of Si, Ge, [1] Te, [2] or AlGaAs, [3] can be used as alternatives to plasmonic structures for realization of low-loss nanophotonic platforms more suitable for real-life practical applications. The particles can subsequently be detached from the substrate to produce a colloidal suspension by placing the sample into a solution that selectively etches the substrate.…”
mentioning
confidence: 99%